Machine-Learning-Assisted Accurate Band Gap Predictions of Functionalized MXene - Rajan, Arunkumar Chitteth; Mishra, Avanish; Satsangi, Swanti; Vaish, Rishabh; Mizuseki, Hiroshi; Lee, Kwang-Ryeol; Singh, Abhishek K. (AMER CHEMICAL SOC, 2018)
MXenes are two-dimensional (2D) transition metal carbides and nitrides, and are invariably metallic in pristine form. While spontaneous passivation of their reactive bare surfaces lends unprecedented functionalities, consequently a many-folds increase in number of possible functionalized MXene makes their characterization difficult. Here, we study the electronic properties of this vast class of materials by accurately estimating the band gaps using statistical learning. Using easily available properties of the MXene, namely, boiling and melting points, atomic radii, phases, bond lengths, etc., as input features, models were developed using kernel ridge (KRR), support vector (SVR), Gaussian process (GPR), and bootstrap aggregating regression algorithms. Among these, the GPR model predicts the band gap with lowest root-mean-squared error (rmse) of 0.14 eV, within seconds. Most importantly, these models do not involve the Perdew-Burke-Ernzerhof (PBE) band gap as a feature. Our results demonstrate that machine-learning models can bypass the band gap underestimation problem of local and semilocal functionals used in density functional theory (DFT) calculations, without subsequent correction using the time-consuming GW approach.
Keywords: EXFOLIATION; STABILITY; CARBIDES; PHASE; MAX